Considering Contemporary Appalachia: Implications for Culturally Competent Counseling - Joshua Elliott; Dana Ripley (Teaching and Supervision in Counseling, 2021)
This article contributes to the counselor education literature by exploring and synthesizing research from aligned fields of study to provide a contemporary characterization of Appalachia for counselor educators and counselors wishing to increase their cultural knowledge base. The article includes sections on specific aspects of the Appalachian experience, including contemporary trends related to population demographics, the impact of poverty, and the prevalence of mental health and substance use issues. Implications for counselors are discussed and suggestions for culturally competent counseling approaches are presented.
Keywords: Appalachian clients; cultural competence; intersectionality